Romaria de Muquém: perfil e motivações dos romeiros - Franzin, Aldemir (2018)
The research describes the Pilgrimage of Muquém: Profile and Motivations of the Pilgrimes, which produces systematic knowledge about this phenomenon that completed 270 years and that moves the Midwest Region of Brazil and attracts a population of 400,000 people. In the contemporary context of the decline of Catholicism and of the secularized society with options of amusement and leisure for individuals, there is a strong search for the Muquem Pilgrimage. We analyze the problem of the research with the question: what is the meaning that pilgrims attribute to the pilgrimage? who is the pilgrim and what profile do they have and what are the motivations that lead them to this feast? We have chosen bibliographies of authors that address this theme, allied to field observation, electronic research, testimonials, letters, tickets, mass intentions, photographs, ex-votos analyzed and information from the researcher to reach the results of the research.